Perioperative management of patients undergoing penile prosthesis surgery in the UK: A survey of current practice. (September 2020) - Ellul, Thomas; Bullock, Nicholas; Steggall, Martin; Brown, Gareth
Objectives: This study aimed to define contemporary perioperative management of patients undergoing penile implant surgery in the UK. Methods: All consultant urological surgeons responsible for the insertion of penile prostheses in the UK were invited to complete an online survey comprising of 25 questions relating to surgeon demographics, patient selection, preoperative work-up, intraoperative management and postoperative care. Anonymised responses underwent descriptive statistical analysis, with particular focus on measures employed to reduce the risk of perioperative infection. Results: Of the 34 invited surgeons, 26 (76.5%) responded to the survey. The majority reported undertaking between 10 and 30 cases in 2018 ( n =17; 65.4%). A total of 23 (88.5%) respondents reported employing a threshold for diabetic control, although the exact limit varied between surgeons. Most respondents ( n =22; 84.6%) reported routinely sampling urine for microscopy, culture and sensitivity. All but one ( n =25; 96.2%) reported routinely performing cavernosal washouts, with the most common solution being a mixture of gentamicin and vancomycin (42.3%). All reported routinely giving intravenous antibiotics on induction of anaesthesia, and although there was no clear consensus, most surgeons preferentially used an aminoglycoside in combination with one other agent (including penicillins or teicoplanin). Conclusion: The variation in current perioperative management demonstrates a potential need for the development and introduction of evidence-based guidelines to standardise practice nationwide. Level of evidence : 5